Effects of action planning and coping planning within the theory of planned behaviour: A physical activity study of patients undergoing haemodialysis - Pakpour, A.; Zeidi, I.; Chatzisarantis, Nikos; Molsted, S.; Harrison, A.; Plotnikoff, R. (Elsevier BV, 2011)
Objective: Patients on dialysis have low physical activity levels. The aim of the study was to examine the validity of action planning and coping planning within the theory of planned behaviour framework, for predicting physical activity behaviour of patients on haemodialysis. Design: This is a prospective study design. Methods: One hundred and forty-four patients who were undergoing haemodialysis were selected from dialysis centres. The mean age of the patients was 56.61 (SD= 11.38) years. The patients completed a questionnaire including variables from the theory of planned behaviour, action planning and coping planning. Physical activity was prospectively assessed at 4-weeks with the validated International Physical Activity Questionnaire self-report measure. A hierarchical regression analysis was performed to examine the effects of action planning and coping planning on physical activity behaviour. Results: There was a main effect for coping planning but not for action planning. Moreover, the analyses resulted in a significant amount of incremental variance accounted for by the interaction of coping planning and intention. Conclusion: Results suggest the combination of high levels of coping planning and intention is associated with increases in physical activity.